Student Team Achievement Division Method To Increase Motivation To Learn The History Of Islamic Culture Class VI - Insani, Isya Mulia (Four Son Scholarship, 2023)
This study aims to determine and analyze the effectiveness of the method of sharing the achievements of student teams in improving student learning motivation in history subjects.MI Terpadu Ar Roihan Lawang, Jalan Monginsidi No. 2 Lawang, Malang through the method of sharing the achievements of the student team used in studying the history of Islamic culture, is expected to overcome a large decrease in motivation because from the perspective that the history of Islamic culture is a complicated and boring lesson, especially in the material know Walisongo. This research is motivated by the number of students who are less enthusiastic about participating in learning activities to get to know Sunan Drajat. Students of Class VI Gaza as a subject of study. During the implementation of the study was conducted three times.Data collection techniques through observation methods, interview methods, and documentation methods. The findings of the study, student learning motivation in the first cycle by 20%, increased in the second cycle by 73.3%, and continues to grow as expected, up to 86.7%, in the third cycle, 13 of 15 students who attended classes have had excellent and good learning motivation. Because the increase in learning motivation has reached more than 75%, it is considered effective and successful